Perception of pregnant women towards midwives: attitude and practice during child delivery in health institutions in Ogbomoso, South-West, Nigeria (Epidemiology, Biostatistics, and Public Health, 2022)
Background: This study aims to ascertain pregnant women’s perceptions of the attitudes and practice of midwives during labour in a mission teaching hospital and a state hospital in Ogbomoso, Southwest Nigeria, and to determine whether or not a relationship exists between patients’perceptions of midwives practice during delivery and the occurrence of neonatal deaths.Methods: The survey was conducted by administering the questionnaire adapted from Caring Behaviour Inventory (CBI) to a random sample of five hundred and seventy nine respondent mothers who gave birth in either a Mission teaching hospital or a state hospital in Ogbomoso, Southwest Nigeria. This standardised questionnaire collects demographic data and patient perceptions of nursing attitudes and practice, ranking patients’ responses to a series of statements about the midwives on a four point Likert scale. Data was analysed using Pearson product moment correlation analyses and multiple regression analyses.Results: Our study revealed that there was a positive response on the attitude and practise of midwives during delivery by the respondents. Secondly, there was a positive impression on the influence of the attitude and practice of midwives during delivery by the respondents.Conclusions: There was no evidence of a relationship between patients’ perceptions of midwives practice during delivery and the occurrence of neonatal deaths.